Using a mentorship model to localise the Practical Approach to Care Kit (PACK): from South Africa to Ethiopia. (19th January 2019) - Feyissa, Yibeltal Mekonnen; Hanlon, Charlotte; Emyu, Solomon; Cornick, Ruth Vania; Fairall, Lara; Gebremichael, Daniel; Teka, Telahun; Shiferaw, Solomon; Walelgne, Wubaye; Mamo, Yoseph; Segni, Hailemariam; Ayehu, Temesgen; et al.
Abstract : The Federal Ministry of Health, Ethiopia, recognised the potential of the Practical Approach to Care Kit (PACK) programme to promote integrated, comprehensive and evidence-informed primary care as a means to achieving universal health coverage. Localisation of the PACK guide to become the 'Ethiopian Primary Health Care Clinical Guidelines' (PHCG) was spearheaded by a core team of Ethiopian policy and technical experts, mentored by the Knowledge Translation Unit, University of Cape Town. A research collaboration, ASSET (he A lth S ystems S tr E ng T hening in sub-Saharan Africa), has brought together policy-makers from the Ministry of Health and health systems researchers from Ethiopia (Addis Ababa University) and overseas partners for the PACK localisation process, and will develop, implement and evaluate health systems strengthening interventions needed for a successful scale-up of the Ethiopian PHCG. Localisation of PACK for Ethiopia included expanding the guide to include a wider range of infectious diseases and an expanded age range (from 5 to 15 years). Early feedback from front-line primary healthcare (PHC) workers is positive: the guide gives them greater confidence and is easy to understand and use. A training cascade has been initiated, with a view to implementing in 400 PHC facilities in phase 1, followed by scale-up to all 3724 health centres in Ethiopia during 2019. Monitoring and evaluation of the Ministry of Health implementation at scale will be complemented by indepth evaluation by ASSET in demonstration districts. Anticipated challenges include availability of essential medications and laboratory investigations and the need for additional training and supervisory support to deliver care for non-communicable diseases and mental health. The strong leadership from the Ministry of Health of Ethiopia combined with a productive collaboration with health systems research partners can help to ensure that Ethiopian PHCG achieves standardisation of clinical practice at the primary care level and quality healthcare for all.